2003
DOI: 10.1074/jbc.m211395200
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Trafficking Efficiency and Functional Properties of ATP-sensitive Potassium Channels through a Single Amino Acid in the Sulfonylurea Receptor

Abstract: Mutations in the sulfonylurea receptor 1 (SUR1), a subunit of ATP-sensitive potassium (K ATP ) channels, cause familial hyperinsulinism. One such mutation, deletion of phenylalanine 1388 (⌬Phe-1388), leads to defects in both trafficking and MgADP response of K ATP channels. Here we investigated the biochemical features of Phe-1388 that control the proper trafficking and function of K ATP channels by substituting the residue with all other 19 amino acids. Whereas surface expression is largely dependent on hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 58 publications
0
22
0
Order By: Relevance
“…B, surface mutant channels rescued by tolbutamide displayed normal response to MgADP and diazoxide after tolbutamide washout. The MgADP or diazoxide response was quantified as described previously (38). First, the response was calculated as the current in a K-INT solution plus 0.1 mM ATP, 0.5 mM ADP or 0.25 mM diazoxide, and 1 mM free Mg 2ϩ , relative to that in plain K-INT solution (see C and D below).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…B, surface mutant channels rescued by tolbutamide displayed normal response to MgADP and diazoxide after tolbutamide washout. The MgADP or diazoxide response was quantified as described previously (38). First, the response was calculated as the current in a K-INT solution plus 0.1 mM ATP, 0.5 mM ADP or 0.25 mM diazoxide, and 1 mM free Mg 2ϩ , relative to that in plain K-INT solution (see C and D below).…”
Section: Discussionmentioning
confidence: 99%
“…Drug treatment was initiated 32-40 h post-transfection and lasted for 4 -24 h. The cells were then processed for chemiluminescence assays as described previously (36,38). Briefly, the cells were fixed with 2% paraformaldehyde for 30 min at 4°C, preblocked in PBS with 0.1% BSA for 30 min, incubated in M2 anti-FLAG antibody (10 g/ml) for an hour, washed four times for 30 min in PBS with 0.1% BSA, incubated in horseradish peroxidase-conjugated anti-mouse (Jackson, 1:1000 dilution) for 20 min, and washed again four times for 30 35 S-Label, 150 -250 Ci/ml) for 30 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, opener binding to SUR1 is detectable, although binding assays showed a 1000-to 10,000-fold difference in dissociation constants for pinacidil, P1075, or levcromakakim between SUR1 and SUR2 isoforms (Schwanstecher et al, 1998). Functional evidence of a low-affinity SUR1 site for nondiazoxide openers has also been presented by Cartier et al (2003) who observed activation of SUR1-based channels by high concentrations of pinacidil after SUR1 had been mutated (F1388L) in NBD2, a region not thought to be directly involved in opener binding.…”
mentioning
confidence: 94%
“…Mutations in both of these genes are associated with disorders of insulin secretion including congenital hyperinsulinism and neonatal diabetes (4, 7). Studies have shown that although some mutations affect the nucleotide regulation of the channel (12-14), others alter the density of the channels at the cell surface by affecting trafficking (15)(16)(17)(18)(19). Recent large scale genome-wide studies have established a strong link between the KCNJ11 gene and type 2 diabetes (20); however, the underlying mechanisms are unknown.…”
mentioning
confidence: 99%